PALATABILITAS PAKAN GAJAH SUMATERA (Elephas Maximus Sumatranus Temminck.) DI DESA PANGKALAN GONDAI KECAMATAN LANGGAM KABUPATEN PELALAWAN PROVINSI RIAU - Farib Hamdani; Defri Yoza; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Sumatran elephant (Elephas maximus sumatranus Temminck), is one of protected fauna.  The Elephants population depends on carrying capacity  of the habitat and feed supply in the area. This study aimed to identified species and palatability of  elephants feed. This study was done in september until december 2016 in around Gondai Village Base Langgam District Pelalawan Regency Riau Province. Based on result from this study the kind of feed often encountered is rumput kawat, alang-alang, rumput teki, and rumput segitiga. From palatability index the species of plant most liked is rumput kawat (Panicum repens), alang-alang (Imperata cylindrica raeusch), rumput teki (Cyperus sp.), and rumput segitiga (Cyperus rotundus). The species plant likes is rumput jarum (chrysopogan aciculata) dan sianik (Cyperus aromaticum), while species dislike is paku harupat (Nephrolepis bisserata), mahang (Macaranga javanica), dan pakis (Stenochlaena sp).  Keywords: Palatability, Feed, Elephas Maximus Sumatranus